Mild anemia is frequent and associated with micro‐ and macroangiopathies in patients with type 2 diabetes mellitus - Ito, Hiroyuki (Blackwell Publishing Ltd, 2010)
Aims/Introduction:  The present study investigated the frequency of mild anemia, which is not an indication of intensive therapy using drugs, in Japanese patients with type 2 diabetes mellitus and the association of mild anemia with diabetic complications. Materials and Methods:  This is a cross‐sectional study of 1189 patients with type 2 diabetes mellitus. Anemia was defined as a hemoglobin level <13.5 g/dL in men and <12.0 g/dL in women. The patients with anemia were divided into two groups: (i) grade 1 anemia with a hemoglobin level ≥11.0 g/dL; and (ii) grade 2 anemia with a hemoglobin level <11.0 g/dL. Results:  The prevalence of anemia increased with the progression of the stage of diabetic nephropathy and chronic kidney disease. The frequencies of diabetic micro‐ and macroangiopathies increased with the progression of anemia among 798 patients without anemia, 300 with grade 1 anemia and 91 with grade 2 anemia. Both grade 1 and grade 2 anemia were associated with diabetic micro‐ and macroangiopathies. They remained independently associated with diabetic retinopathy, coronary heart disease and peripheral arterial disease after adjustment by age, sex, body mass index, use of angiotensin II receptor blocker, estimated glomerular filtration rate and stage of diabetic nephropathy. Conclusions:  Mild anemia is frequent and associated with micro‐ and macroangiopathies in patients with type 2 diabetes mellitus. It is important to carry out intensive examinations for the detection of diabetic micro‐ and macroangiopathies in addition to evaluating the causes of anemia when mild anemia is found in patients with diabetes mellitus. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2010.00060.x, 2010)